Hey there! :D
1. c - 7 = 32
To solve this problem, add the difference and the subtrahend of the given equation.
[tex]32 + 7 = \boxed{\sf 39}[/tex]
Checking:
To check, simply substitute the conclusion on the unknown quantity.
39 (c) - 7 = 32
Thus, the equation was correct which gives us the answer that:
[tex]\large \boxed{ \sf {\: c = 39}}[/tex]
[tex]\begin{gathered} \\ \end{gathered}[/tex]
2. r + 4 = 39
To solve this problem, subtract the sum and the addend of the given equation.
[tex]39 - 4 = \boxed{\sf 35}[/tex]
Checking:
To check, simply substitute the conclusion on the unknown quantity.
35 (r) + 4 = 39
Thus, the equation was correct which gives us the answer that:
[tex]\large\boxed{ \sf {r \: = \: 35}}[/tex]